Case report: Sacral agenesis in two boxer dogs: clinical presentation, diagnostic investigations, and outcome - Dell'Apa, Diletta; Fumeo, Martina; Volta, Antonella; Bernardini, Marco; Fidanzio, Francesca; Buffagni, Valentina; Christen, Matthias; Jagannathan, Vidhya; Leeb, Tosso; Bianchi, Ezio (Frontiers in Veterinary Science, 2023)
Two boxer dogs from the same litter were presented at 3 months of age for urinary and fecal incontinence. Both dogs had an abnormal tail consisting of a small stump, an atonic anal sphincter, and absent perineal reflex and sensation. Neurological evaluation was indicative of a lesion of the cauda equina or sacral spinal cord. Radiology and CT scan of the spine displayed similar findings in the two dogs that were indicative of sacral agenesis. Indeed, they had 6 lumbar vertebrae followed by a lumbosacral transitional vertebra, lacking a complete spinous process, and a hypoplastic vertebra carrying 2 hypoplastic sacral transverse processes as the only remnant of the sacral bone. Caudal vertebrae were absent in one of the dogs. On MRI, one dog had a dural sac occupying the entire spinal canal and ending in a subfascial fat structure. In the other dog, the dural sac finished in an extracanalar, subfascial, well-defined cystic structure, communicating with the subarachnoid space, and consistent with a meningocele. Sacral agenesis—that is the partial or complete absence of the sacral bones—is a neural tube defect occasionally reported in humans with spina bifida occulta. Sacral agenesis has been described in human and veterinary medicine in association with conditions such as caudal regression syndrome, perosomus elumbis, and Currarino syndrome. These neural tube defects are caused by genetic and/or environmental factors. Despite thorough genetic investigation, no candidate variants in genes with known functional impact on bone development or sacral development could be found in the affected dogs. To the best of the authors' knowledge, this is the first report describing similar sacral agenesis in two related boxer dogs.